Analysis of the Functions of Plants in the Literature―Taking Nettles by Alice Munro as an Example - Wang, Yibei (Journal of Theory and Practice in Linguistics, 2024)
Alice Munro (1931-) is famous as a short story writer worldwide. This study is an analysis of Alice Munro’s short story “Nettles”, focusing on the functions of plants in this story. “Nettles” is a type of story from the collection of Hateship, Friendship, Courtship, Loveship, and Marriage. Nettle is a kind of plant, and Munro used it as a title, which caused it to have deep meanings. While studying plant images, we have more perspectives from which to study Munro’s stories. Plants can evoke emotional responses in a story, so this paper is a conscious effort to study the connections and connotations between plants and the writer’s main idea. To study images to learn epiphany for middle-aged women, love, marriage, and relationships between people. Munro uses metaphor (figure of speech) and uses “Nettles” as the title and the key throughout the story. There are main meanings and functions of nettle’s images in this story: the symbol of normal women (especially middle-aged women), the value and effect in modern society of women, and unexpected frustration or misery in life (because it is a kind of stinging plant). This paper focuses on analyzing the details of text and learning the functions of plant images in this short story. While combining the plant image with the narrator’s life experiences and the author’s writing background and intention, this paper studies Munro’s “Nettles” from a new perspective.